1986
DOI: 10.1021/jm00159a006
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dihydro-2-phenyl-2H-pyrano[2,3-b]pyridines with potent antirhinovirus activity

Abstract: A general synthesis to the title compounds 1, substituted in the 6-position and on the phenyl ring, is outlined. Eighteen analogues were compared with respect to in vitro activity against rhinovirus types 1A, 9, and 64. Compounds 1c and 1h, the 6-bromo- and 6-(methylsulfonyl)-3',4'-dichlorophenyl analogues, afforded median MIC50 values against 23 rhinovirus serotypes of 0.05 and 0.13 micrograms/mL, respectively. Mice dosed orally with 200 mg/kg of 1c or 1h exhibited serum levels well in excess of each compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…15) were identified as potent inhibitors of rhinovirus replication with median plaque EC 50 values of respectively 0.03, 0.006, and 0.006 mg/mL against 32 serotypes of rhinovirus tested. 163,164 Mechanism of action studies with MDL 20,610 indicated that the compound binds directly to the capsid with subsequent inhibition of uncoating. 165 …”
Section: Dibenzofuran and Dibenzosuberol Derivativesmentioning
confidence: 99%
“…15) were identified as potent inhibitors of rhinovirus replication with median plaque EC 50 values of respectively 0.03, 0.006, and 0.006 mg/mL against 32 serotypes of rhinovirus tested. 163,164 Mechanism of action studies with MDL 20,610 indicated that the compound binds directly to the capsid with subsequent inhibition of uncoating. 165 …”
Section: Dibenzofuran and Dibenzosuberol Derivativesmentioning
confidence: 99%
“…3) and 6-Chloro-2-(4-Chlorophenyl)-3,4-Dihydro-2H-1-Benzopyran (BW683C, Fig. 1) were synthesized by published methods (Bargar et al, 1986;Hopkins, 1982). Compound 2-(3,4-Dichlorophenoxy)-5-(Methylsulfonyl)Pyridine (MDL 055, Fig.…”
Section: Test Compoundsmentioning
confidence: 99%
“…As the core intermediates to obtain 4-[(N-imidazol-2-ylmethyl)anilino]pyranopyridine derivatives, 4 types of 2,2-dimethyl-2H-1-pyranopyridines (8)(9)(10)(11)(12)(13)(16)(17)(18)(19)(20), [3,2-c], [3,2-b], [2,3-c], and [2,3-b], were prepared (Scheme 1). 7 To eliminate one of the chiral centers, we introduced dimethyl function at the 2-position instead of an acetal of 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Because the treatment of 2-pyridinol with 3-chloro-3-methylbut-1-yne didn't give the desired O-alkylation product, alternative method was employed for the synthesis of the [2,3-b]isomers. The reaction of 3,5-dibromo-2-methoxypyridine 14 10 with n-BuLi and 3-methyl-2-butenal gave the allylic alcohol 15, followed by the treatment with 48% HBr in acetic acid provided the pyrano [2,3-b]pyridine 16. The bromine of pyranopyridines was further converted to nitrile via nucleophilic substitution with CuCN under microwave irradiation, or debrominated using n-BuLi.…”
Section: Chemistrymentioning
confidence: 99%